Temporal observations of a linear sand dune in the Simpson Desert, central Australia: Testing models for dune formation on planetary surfaces. Issue 10 (30th October 2015) - Craddock, Robert A.; Tooth, Stephen; Zimbelman, James R.; Wilson, Sharon A.; Maxwell, Ted A.; Kling, Corbin
Abstract: Linear dunes are the most common dune form found on planetary surfaces, yet questions remain about their formation. Temporal observations of a linear dune located in the Simpson Desert of central Australia were made to monitor dune movement and to test competing hypotheses regarding linear dune formation. Our observations were collected on three separate occasions from 2006 to 2014. Rebar stakes were placed in a gridded pattern so that multiple measurements of sand thickness, GPS surveys, and photographs could be taken at the same locations over time. We observed widespread reworking of sand on and around the dune crest, with sand accumulation locally exceeding a meter between surveys. Overall, the height of the dune crest increased by several centimeters. We also observed fluctuations in the sand cover in the adjacent swales that often exceeded 2–3 cm between surveys, yet we did not observe any appreciable changes in the position of the dune's downwind terminus. Weather data indicate that the effective sand‐transporting winds in the Simpson are widely unimodal. Net sediment flux (resultant drift direction) is toward the north‐northwest, locally at an oblique angle to dune orientation. Collectively, our results suggest that the linear dune is actively maintained by vertical accretion. The implications from our observations are that linear dunes on other planetary surfaces could form in wind regimes that are widely unimodal, even where the resultant drift direction is locally oblique to dune orientation. In particular, such findings may provide support for global circulation models of Titan. Key Points: A linear dune was monitored over an 8 year period The linear dune has mainly accreted vertically with little linear extension These observations support global circulation models for Titan